Development of HepG2-derived cells expressing cytochrome P450s for assessing metabolism-associated drug-induced liver toxicity. (5th August 2016) - Xuan, Jiekun; Chen, Si; Ning, Baitang; Tolleson, William H.; Guo, Lei
Abstract: The generation of reactive metabolites from therapeutic agents is one of the major mechanisms of drug-induced liver injury (DILI). In order to evaluate metabolism-related toxicity and improve drug efficacy and safety, we generated a battery of HepG2-derived cell lines that express 14 cytochrome P450s (CYPs) (1A1, 1A2, 1B1, 2A6, 2B6, 2C8, 2C9, 2C18, 2C19, 2D6, 2E1, 3A4, 3A5 and 3A7) individually using a lentiviral expression system. The expression/production of a specific CYP in each cell line was confirmed by an increased abundance of the CYP at both mRNA and protein levels. Moreover, the enzymatic activities of representative CYPs in the corresponding cell lines were also measured. Using our CYP-expressed HepG2 cells, the toxicity of three drugs that could induce DILI (amiodarone, chlorpromazine and primaquine) was assessed, and all of them showed altered (increased or decreased) toxicity compared to the toxicity in drug-treated wild-type HepG2 cells. CYP-mediated drug toxicity examined in our cell system is consistent with previous reports, demonstrating the potential of these cells for assessing metabolism-related drug toxicity. This cell system provides a practical in vitro approach for drug metabolism screening and for early detection of drug toxicity. It is also a surrogate enzyme source for the enzymatic characterization of a particular CYP that contributes to drug-induced liver toxicity. Highlights: We developed a battery of HepG2-derived cell lines that express 14 individual CYPs. We confirmed the functionality of the CYPs at the mRNA, protein and enzymatic activity levels. We examined the metabolism-related toxicity of three drugs in our cell system.